Expression of polycomb protein BMI-1 1 maintains the plasticity of basal 2 bronchial epithelial cells - Torr, Elizabeth; Heath, Meg; Mee, Maureen; Shaw, Dominick E.; Sharp, Tyson V.; Sayers, Ian (Wiley, 2016)
The airway epithelium is altered in respiratory disease and is thought to contribute to disease aetiology. A caveat to disease research is that the technique of isolation of bronchial epithelial cells from patients is invasive and cells have a limited lifespan. The aim of the current study was to extensively characterise the plasticity of primary human bronchial epithelial cells that have been engineered to delay cell senescence including the ability of these cells to differentiate. Cells were engineered to express BMI-1 or hTERT using viral vector systems. Cells were characterised at passage (p) early (p5), mid (p10) and late (p15) stage for; BMI-1, p16 and CK14 protein expression, viability and the ability to differentiate at air-liquid interface (ALI), using a range of techniques including immunohistochemistry (IHC), immunofluorescence (IF), transepithelial electrical resistance (TEER), Scanning Electron Microscopy (SEM), (MUC5AC and beta tubulin (BTUB) staining). BMI-1 expressing cells maintained elevated levels of the BMI-1 protein and the epithelial marker CK14 and showed a suppression of p16. BMI-1 expressing cells had a viability advantage, differentiated at ALI and had a normal karyotype. In contrast hTERT expressing cells had a reduced viability, showed limited differentiation and had an abnormal karyotype. We therefore provide extensive characterisation of the plasticity of BMI-1 expression cells in the context of the ALI model. These cells retain properties of wild-type cells and may be useful to characterise respiratory disease mechanisms in vitro over sustained periods.